2018
DOI: 10.1039/c7ra13387a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Lewis acid and a Brønsted acid on the conversion of microcrystalline cellulose into 5-hydroxymethylfurfural in a single-phase reaction system of water and 1,2-dimethoxyethane

Abstract: -Hydroxymethylfurfural (HMF) is a typical dehydration product of C6 carbohydrates, and it can be converted into a series of chemicals and liquid fuels. In this study, an advanced low-boiling single-phase reaction system consisting of water and 1,2-dimethoxyethane (DMOE) was proposed for the production of HMF from microcrystalline cellulose (MCC). AlCl 3 and H 3 PO 4 were selected as the Lewis acidic catalyst and Brønsted acidic catalyst, respectively, and the influence of these two catalysts on the conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Production of fructose by these methods is being performed in aqueous media as well as in organic solvents. This could include a 2‐step process using organic alcohol as a solvent and a bifunctional Lewis and Brønsted acid catalyst for the in‐situ ketalization of fructose and the consequent hydrolysis upon addition of H 2 O . Saravanamurugan et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of fructose by these methods is being performed in aqueous media as well as in organic solvents. This could include a 2‐step process using organic alcohol as a solvent and a bifunctional Lewis and Brønsted acid catalyst for the in‐situ ketalization of fructose and the consequent hydrolysis upon addition of H 2 O . Saravanamurugan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Another method uses Lewis acid catalysts in which the isomerization reaction occurs by intramolecular hydride shift . Production of fructose by these methods is being performed in aqueous media as well as in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Ionic liquid has superior ability in biomass solvation, so it has been widely utilized as an advanced solvent in the hydrothermal conversion of biomass. 20 However, the potential of ionic liquid in practical application was restricted due to its much higher cost than traditional organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the solvent molecules may combine with reactants or intermediates, which could affect the stabilization of intermediates and transition states. 20 However, the potential of ionic liquid in practical application was restricted due to its much higher cost than traditional organic solvent. Recently, single-phase solvent system made up of water and organic solvent has been found to hinder side reactions to a certain degree and to raise furfural yields notably.…”
mentioning
confidence: 99%
“…Li et al reported an efficient niobia/carbon catalyst (Nb/C-50, 50 wt% of Nb 2 O 5 ) prepared from niobium tartrate (Nb 2 O 5 ) and glucose as raw materials via carbonization, for the conversion of cellulose into 5-HMF, leading to 53.3% HMF yield and 77.8% total carbon yield in the THF/H 2 O biphasic system at 170°C for 8 h (Table 5, entry 4)[336]. What is noteworthy is that the Nb/C-50 catalyst was agglomerated particles and contained suitable Brønsted/Lewis acid sites and weak to medium acid strength, which favored the conversion of cellulose to 5-HMF.Zhao et al reported an interesting bifunctional catalytic system using AlCl 3 as the Lewis acidic catalyst and H 3 PO 4 as Brønsted acidic catalyst, and when the AlCl 3 -H 3 PO 4 catalyst was employed for the transformation of cellulose to 5-HMF, the highest yield of 5-HMF with 49.42% was achieved in a single-phase reaction system of 1,2-dimethoxyethane (DMOE) and water at 180°C for 120 min under the reaction conditions of mole ratio of 1: 0.8 of AlCl 3 / H 3 PO 4 and volumetric ratio of 7: 1 of DMOE/H 2 O (Table 5, entry 5)[337].…”
mentioning
confidence: 99%